Energy Management in Higher Education Institutions: A Bibliometric Analysis of Past and Future Research Trends - Rantau Gelora Leonardo Juniko; Gusman Nawanir (Universitas KH. Abdul Chalim Mojokerto, 2025)
This article discusses energy management in higher education institutions using bibliometric analysis to understand past and future research trends, so that future energy needs can be met. This review uses a bibliometric approach, involving 2,266 journals obtained from Web of Science, using two science mapping approaches, namely co-citation analysis and co-word analysis. This is done to investigate the past knowledge structure and future research directions on energy management in higher education institutions. Current research trends on energy management focus on developing frameworks and strategic implementations by considering certain important factors and decision-making strategies. In the future, articles on energy management will focus more on the overall framework and efficiency strategies in implementing energy management in higher education institutions, along with how to anticipate obstacles in its implementation. This article provides benefits for researchers and decision-making practitioners on energy management, by increasing understanding of implementing energy management in higher education institutions. This article provides results and conclusions that can be used by decision-makers in higher education institutions to implement effective and efficient energy management and encourage continuous improvement in higher education institutions.